2004
DOI: 10.1007/s00330-004-2240-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective intra-arterial chemoembolization of pelvic and spine bone metastases

Abstract: The purpose of this study was to determine the effect of interventional palliative therapy by using chemoembolization on metastatic bone pain and tumor bulk in inoperable metastases where chemotherapy and radiotherapy had failed. Twenty-five patients (mean age: 59 years) underwent chemoembolization of symptomatic lytic lesions involving the spinal column (n=10), iliac bone and sacrum (n=15). The study design consisted of at least three procedures based on combined chemoembolization performed under analog-sedat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 22 publications
3
14
0
7
Order By: Relevance
“…Sur cette base, certains auteurs, encouragés par le succès de l'embolisation, ont développé des techniques de perfusion intra-artérielle d'antimitotiques ou de chimioembolisation qui associent chimiothérapie intra-artérielle et embolisation hypersélective [31].…”
Section: Techniques Endovasculairesunclassified
See 1 more Smart Citation
“…Sur cette base, certains auteurs, encouragés par le succès de l'embolisation, ont développé des techniques de perfusion intra-artérielle d'antimitotiques ou de chimioembolisation qui associent chimiothérapie intra-artérielle et embolisation hypersélective [31].…”
Section: Techniques Endovasculairesunclassified
“…Quoi qu'il en soit, une réponse partielle ou complète est observée dans 50 à 70 % des cas, et cette méthode s'avère souvent efficace dans la prise en charge des métastases pré-valentes non accessibles aux autres traitements locaux [31].…”
Section: Embolisation Endovasculaireunclassified
“…Some patients present with painful bone lesions, fracture, or spinal cord compression. Experience with bone metastases from tumors other than MTC have demonstrated that percutaneous methods of treatment such as cementoplasty (image-guided injection of polymethyl metacrylate cement in bones), thermal ablation (radiofrequency or cryotherapy) and arterial embolization followed by surgery, or a combination of these methods, have been associated with pain reduction and bone consolidation[25,26,27,28,29,30,31,32]. Isolated bone metastases may be surgically resected or treated with percutaneous methods, but it is extremely uncommon for these patients to be rendered free of disease.…”
Section: Local Treatment Modalities For Distant Metastasesmentioning
confidence: 99%
“…Chiras et al described a series of 25 patients with metastatic disease to the spinal column (n = 10), iliac bone and sacrum (n = 15) who were treated with transarterial chemoembolization using polyvinyl alcohol particles, pirarubicin, and carboplatin, achieving significant pain relief in 15 patients and local tumor control in 16 patients with available imaging follow-up. 6 There are two main differences between this protocol and ours: 1) our technique does not involve the use of embolic agents and consists of chemotherapy infusion only; and 2) the focus of our treatment is the epidural disease and neurological symptoms as opposed to pain levels and overall tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our approach, Chiras et al used a single therapeutic agent for treating bone metastatic disease caused by a variety of tumors. 6 Ideally, each tumor could have been targeted with a separate chemotherapy agent, but this approach requires separate protocols, investigational new drug approvals, and trials for each drug. Given the low rate of accrual and the strict indications, it would take many years before such trials would be completed.…”
Section: Discussionmentioning
confidence: 99%